2021
DOI: 10.1038/s41467-021-27227-2
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 effectors facilitate generation of single-sex litters and sex-specific phenotypes

Abstract: Animals are essential genetic tools in scientific research and global resources in agriculture. In both arenas, a single sex is often required in surplus. The ethical and financial burden of producing and culling animals of the undesired sex is considerable. Using the mouse as a model, we develop a synthetic lethal, bicomponent CRISPR-Cas9 strategy that produces male- or female-only litters with one hundred percent efficiency. Strikingly, we observe a degree of litter size compensation relative to control mati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Research into gene editing is pursuing gender-specific markers to support early detection and even to actively sex, that is to create all-female or allmale offspring. A 2021 paper in Nature Communications indicated that scientists employing the gene editing technology CRISPR-Cas9 have created female-only and male-only mice litters, a procedure with great relevance for the poultry layer industry (Douglas et al, 2021). The CRISPR-Cas9 genome editing technique is built upon CRISPR, a family of DNA sequences found in the genomes of prokaryotic organisms such as bacteria, and Cas9, an enzyme that uses CRISPR sequences as a guide to recognize and cleave specific strands of DNA that are complementary to the CRISPR sequence.…”
Section: Re-sexingmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into gene editing is pursuing gender-specific markers to support early detection and even to actively sex, that is to create all-female or allmale offspring. A 2021 paper in Nature Communications indicated that scientists employing the gene editing technology CRISPR-Cas9 have created female-only and male-only mice litters, a procedure with great relevance for the poultry layer industry (Douglas et al, 2021). The CRISPR-Cas9 genome editing technique is built upon CRISPR, a family of DNA sequences found in the genomes of prokaryotic organisms such as bacteria, and Cas9, an enzyme that uses CRISPR sequences as a guide to recognize and cleave specific strands of DNA that are complementary to the CRISPR sequence.…”
Section: Re-sexingmentioning
confidence: 99%
“…The CRISPR-Cas9 genome editing technique is built upon CRISPR, a family of DNA sequences found in the genomes of prokaryotic organisms such as bacteria, and Cas9, an enzyme that uses CRISPR sequences as a guide to recognize and cleave specific strands of DNA that are complementary to the CRISPR sequence. The development of the CRISPR-Cas9 genome editing technique was recognized by the Nobel Prize in Chemistry in 2020, with the findings hailed by the poultry industry as 'a genetic solution for the male chick layer dilemma' (Douglas et al, 2021). A senior lecturer in molecular genetics and reproduction described to a poultry industry news site that: 'We have developed a method for 100% efficient sex selection of offspring sex in mice, and we believe this will be readily adaptable to other species including livestock, should public opinion and legislation allow for the use of this type of genetic technology in the food chain' (Douglas et al, 2021).…”
Section: Re-sexingmentioning
confidence: 99%
“…There is also a prospect of “consumer eugenics”, which are eugenics driven by parental choice rather than by state order, which would have similar results to traditional eugenics, such that ethicists are concerned that unequal access to such technologies could lead to genetic classism. The latest CRISPR-Cas9 research can produce male- or female-only litters with 100 percent efficiency [ 63 ], which has a potential risk to exacerbate the gender imbalance of the global population in the future if it is applied to humans. Meanwhile, it is common evolutionary knowledge that organisms, including humans, require a high level of genetic diversity.…”
Section: Challenge Of Governing Human Germline and Heritable Genome E...mentioning
confidence: 99%
“…A recent development may make this manner of sexing possible in the future. In December 2021, Douglas et al (2021) published a study in which they used mice prototypes and succeeded in producing only males or only females. This new method involves a two-step genetic manipulation procedure that inactivates embryos shortly after fertilisation, as a result of which only the desired sex can develop.…”
Section: Genetic Manipulationmentioning
confidence: 99%
“…When combined with a mother line carrying the trigger gene, this leads to all male offspring (carrying XY chromosomes) having both the lethal and the trigger gene, and failing to develop. Douglas et al (2021) see opportunities for extending these gene techniques for managing offspring sex also to poultry. The researchers are currently talking to the Roslin Institute (UK) about setting up preliminary pilot tests (Mcdougal, 2021).…”
Section: Genetic Manipulationmentioning
confidence: 99%